Significant effect of oxygen atmosphere on the structure, optical and electrical properties of Ti-doped In2O3 transparent conductive thin films - Dong, C.J.; Yu, W.X.; Xu, M.; Chen, C.; Song, Z.Y.; Li, L.; Wang, Y.D. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Titanium-doped indium oxide (In2O3) transparent conductive thin films were deposited on glass and sapphire (0001) substrates with/without oxygen atmosphere by DC magnetron sputtering at 300 °C. The content of titanium is estimated to be about 1.8 at.% using energy dispersive spectroscopy. The smooth surfaces were covered with more uniform octahedral grains. X-ray diffraction measurements indicated that the preferential growth orientation along the (400) plane for the sample grown without oxygen atmosphere shifts to (222) for the sample grown in the oxygen atmosphere. The average optical transmittance of the sample grown with the introduction of oxygen varies from 70% to 90% in the visible region, which corresponds well to the variation of carrier and mobility. Hence, both intermediate dopant and oxygen atmosphere will provide the optimum balance between carrier concentration and mobility leading to the best transport properties of Ti-doped In2O3 films.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 765-775
Keywords: optyka; transparent oxide; indium oxide; thin films; electrical properties; optical properties